2020
DOI: 10.1074/jbc.ra120.013206
|View full text |Cite
|
Sign up to set email alerts
|

An aberrantly sustained emergency granulopoiesis response accelerates postchemotherapy relapse in MLL1-rearranged acute myeloid leukemia in mice

Abstract: Acute myeloid leukemia (AML) with mixed lineage leukemia 1 (MLL1) gene rearrangement is characterized by increased expression of a set of homeodomain transcription factors, including homeobox A9 (HOXA9) and HOXA10. The target genes for these regulators include fibroblast growth factor 2 (FGF2) and Ariadne RBR E3 ubiquitin ligase 2 (ARIH2). FGF2 induces leukemia stem cell expansion in MLL1-rearranged AML. ARIH2 encodes TRIA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Point mutations, amplifications, and translocations of Runx1 are often associated with leukemia ( De Braekeleer et al., 2009 ; Niini et al., 2000 ; Osato, 2004 ; Otalora-Otalora et al., 2019 ). Hoxa9 and Hoxa10 are highly expressed in acute myeloid leukemias ( Collins and Hess, 2016 ; Lambert et al., 2019 ; Shah et al., 2016 ; Wang et al., 2020 ). Interestingly, the iR1A9A10-ESC-derived iHPC recipients showed no leukemogenesis and tumors over time.…”
Section: Discussionmentioning
confidence: 99%
“…Point mutations, amplifications, and translocations of Runx1 are often associated with leukemia ( De Braekeleer et al., 2009 ; Niini et al., 2000 ; Osato, 2004 ; Otalora-Otalora et al., 2019 ). Hoxa9 and Hoxa10 are highly expressed in acute myeloid leukemias ( Collins and Hess, 2016 ; Lambert et al., 2019 ; Shah et al., 2016 ; Wang et al., 2020 ). Interestingly, the iR1A9A10-ESC-derived iHPC recipients showed no leukemogenesis and tumors over time.…”
Section: Discussionmentioning
confidence: 99%
“…The genetic characteristic of MLL is the chromosome 11q23 abnormality, Frontiers in Physiology frontiersin.org and this type of leukemia is associated with adverse prognosis. Emergency granulopoiesis is known to accelerate leukemogenesis in MLL1-rearranged AML and this occurs in an RTK-dependent manner (Wang et al, 2020). Moreover, it has been reported that in MLL1-ELL AML mice, TRIAD1 expression is decreased, contributing to sustained RTK signaling and failing to terminate emergency granulopoiesis (Figure 4) (Wang et al, 2018;Wang et al, 2020).…”
Section: Effects Of E3 Ubiquitin Ligases On Rtk Signalingmentioning
confidence: 99%
“…Emergency granulopoiesis is known to accelerate leukemogenesis in MLL1-rearranged AML and this occurs in an RTK-dependent manner (Wang et al, 2020). Moreover, it has been reported that in MLL1-ELL AML mice, TRIAD1 expression is decreased, contributing to sustained RTK signaling and failing to terminate emergency granulopoiesis (Figure 4) (Wang et al, 2018;Wang et al, 2020). Using TRIAD1-substrate RTKs inhibitors can terminate emergency granulopoiesis, delay leukemogenesis during emergency granulopoiesis, and normalize innate immune responses when combined with chemotherapy (Table 2) (Wang et al, 2020).…”
Section: Effects Of E3 Ubiquitin Ligases On Rtk Signalingmentioning
confidence: 99%
See 2 more Smart Citations